2018
DOI: 10.1038/s12276-018-0154-6
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondrial proteome profile indicative of type 2 diabetes mellitus in skeletal muscles

Abstract: The pathogenesis of type 2 diabetes mellitus (T2DM) is closely associated with mitochondrial functions in insulin-responsive tissues. The mitochondrial proteome, compared with the mitochondrial genome, which only contains 37 genes in humans, can provide more comprehensive information for thousands of mitochondrial proteins regarding T2DM-associated mitochondrial functions. However, T2DM-associated protein signatures in insulin-responsive tissues are still unclear. Here, we performed extensive proteome profilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 72 publications
7
33
0
Order By: Relevance
“…Other experimental evidence also supports the hypothesis that dioxins impair β-cell function 39,40 or induces vascular inflammation 41 in mice. Proteomic analysis of mitochondria from skeletal muscles of diabetes patients showed that subunits of oxidative phosphorylation were downregulated 42 . Transcriptome profiling revealed that a number of genes responsible for mitochondria ATP synthesis, oxidative phosphorylation, or mitochondrial dynamics were downregulated in human diabetes islets or β-cells 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Other experimental evidence also supports the hypothesis that dioxins impair β-cell function 39,40 or induces vascular inflammation 41 in mice. Proteomic analysis of mitochondria from skeletal muscles of diabetes patients showed that subunits of oxidative phosphorylation were downregulated 42 . Transcriptome profiling revealed that a number of genes responsible for mitochondria ATP synthesis, oxidative phosphorylation, or mitochondrial dynamics were downregulated in human diabetes islets or β-cells 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the 335 differentially regulated mitochondrial proteins, 135 proteins were upregulated in T2D compared with the nondiabetic controls, whereas 200 proteins were downregulated (Figure 3). The proteins upregulated in patients with T2D were mainly involved in processes related to molecular transport and cytoskeletal organization, while Chae et al showed a significant downregulation of several proteins in metabolic pathways, including the TCA cycle, fatty acid oxidation, and glycolysis, and in T2D patients [117]. Interestingly, OXPHOS proteins were represented both among the upregulated and downregulated proteins (6 and 16 proteins, respectively), suggesting an overall altered metabolic activity in patients with T2D, when compared to healthy individuals.…”
Section: Altered Mitochondrial Proteomes In Obesity and Type 2 Diabetesmentioning
confidence: 99%
“…In a more recent study [117], Chae et al published the, so far, most comprehensive mitochondrial proteome of human skeletal muscle. Chae and co-authors implemented ultra-high-pressure nano-LC-ESI-MS/MS on isolated mitochondria from skeletal muscle of T2D patients and non-diabetic control individuals and identified 1671 proteins in at least half of the 10 samples [117]. Of these proteins, 1150 mitochondrial proteins (69%) were represented by two or more peptides (Figure 2).…”
Section: Discovery-mode Proteomics Of Whole Muscle and Isolated Mitocmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the authors established that complex IV (CIV) is a common target for the mitochondrial remodelling induced by ageing or type 2 diabetes [76]. The study of proteomic profiles provides unique information about thousands of mitochondrial proteins that can be used to assess mitochondrial functions that are related to the development of type 2 diabetes [78]. The large size of the proteome indicates that many metabolic and cellular pathways are active in mitochondria.…”
Section: Mitoproteomics In the Treatment Of Insulin Resistancementioning
confidence: 99%